TOWARDS A NOVEL APPROACH HEALING LANGUAGE RIGHTS OF MINORITY: THE CASE OF SRI LANKA - Bawa, Mohamed Mowjoon Atham (UI Scholars Hub, 2013)
Sri Lanka is a multi cultural country comprises of five main ethnic groups: Sinhalese, Tamils, Moors, Malays and Burgher. Language and ethnic heritage distinguish these groups. The Sinhalese are the largest ethnic group in the country comprising 74.5 percent of the population and 99.5 percent of this population are Buddhists and speak Sinhala. The Tamils are approximately 16.5 percent of the population use Tamil as their native language. The Moors constitute around 7.9 percent of the population, 95 percent of them speak the Tamil language. The Malays who originated in Southeast Asia comprise of 0.41 percent of the total population and speak Malay, Tamil, Sinhala and English. Finally, Burghers make up of 0.3 percentage of the Sri Lankan population. They are of European ancestry and have remained Christians and speak English and Sinhala. In Sri Lanka, language is one of the key contributing factors in representing the ethnic identity and concerns about national language have been influential in both cultural and political sphere; it has been the major cause of strife between the Sinhalese and the Tamil speaking population. The impact of language divide remains influential even after the cessation of hostilities and the ending of the civil war. This paper will focus on the critical evaluation of language rights as a key element of the second generation of human rights; economic, social and cultural rights (ESCR). The paper will also explore the underpinnings of ESCRs and its particular application to language rights of the Tamil speaking minority and will examine the various legislative attempts to protect language rights of the Tamil speaking minority and identify the reasons for the failure of those initiatives and will propose effective mechanisms for implementing language rights.